Plasma Symmetric Dimethylarginine Concentration in Dogs with Acute Kidney Injury and Chronic Kidney Disease. (30th March 2017) - Dahlem, D.P.; Neiger, R.; Schweighauser, A.; Francey, T.; Yerramilli, M.; Obare, E.; Steinbach, S.M.L.
Abstract : Background: Symmetric dimethylarginine (SDMA) is considered a biomarker for early detection of renal dysfunction in human patients with acute kidney injury (AKI). At present, no studies exist analyzing the relevance of SDMA in dogs with AKI. Hypothesis/objectives: SDMA would correctly identify dogs with renal disease but would not be able to differentiate between AKI and CKD. Animals: Eighteen healthy control dogs, 48 dogs with AKI, and 29 dogs with CKD. Methods: Prospective study. Dogs with kidney disease were categorized as having AKI or CKD according to the history, clinical signs, laboratory findings, and results of diagnostic imaging. Plasma SDMA concentration was measured by IDEXX Laboratories. SDMA/creatinine ratio was calculated in dogs with AKI or CKD. Results: Median SDMA concentrations were 8.5 μg/dL (6–12 μg/dL), 39.5 μg/dL (8–>100 μg/dL), and 35 μg/dL (12–>100 μg/dL), in healthy, AKI, and CKD, respectively. SDMA concentrations were significantly higher in dogs with AKI ( P < .0001) or CKD ( P < .0001) in comparison with healthy dogs. Median SDMA/creatinine ratio in dogs with AKI and CKD was 6.5 (1.7–20.9) and 10 (2.4–33.9) ( P = .0004), respectively. Although there was overlap of the SDMA/creatinine ratio in dogs with AKI or CKD, it was significantly higher in dogs with CKD compared to dogs with AKI ( P = .0004). Conclusions and Clinical Importance: In this population, SDMA was suitable for identifying dogs affected by AKI or CKD, but could not differentiate between them.